Hyperthyrotropinaemia in untreated subjects with down's syndrome aged 6 months to 64 years: a comparative analysis - Meyerovitch, Joseph; Antebi, Felice; Greenberg-Dotan, Sari; Bar-Tal, Ornit; Hochberg, Ze'ev (Archives of disease in childhood, 2012)
Objectives To determine whether an altered hypothalamic-pituitary-thyroid axis is inherent to Down's syndrome or if a high level of thyroid-stimulating hormone (TSH) is a feature in a subset of patients with Down's syndrome. Design Comparative analysis. Setting Major health maintenance organisation (3.8 million insured). Patients A data warehouse search identified all subjects with Down's syndrome who attended Clalit Health Services in 2006 and were tested for TSH and free thyroxine (T4) level on the day of diagnosis (intention-to-treat population). The study group consisted of patients who were not diagnosed with thyroid disease or did not receive thyroid-modulating medication (n=428). Their findings were compared with a control group of healthy age- and sex-matched subjects who were randomly selected from the general population. Main outcome measures Distribution of free T4, TSH and total T3 levels. Results The distribution plot for TSH showed a significant shift of the curve to higher values in the study group compared with the controls (p≤0.0001). This finding held true on further analysis of the whole intention-to-treat population (p<0.006). The free T4 distribution curve also shifted significantly to higher levels in patients with Down's syndrome (p≤0.0001). Conclusions Down's syndrome is associated with higher TSH levels. The results suggest that hyperthyrotropinaemia is an innate attribute of chromosome 21 trisomy. Therefore, T4 treatment should not be contemplated in Down's Syndrome unless the TSH is >95th centile in the presence of normal-range free T4 levels.